Mecanismos de autenticação e controle de acesso para uma arquitetura de Internet do Futuro - Melo, Pedro Henrique Aparecido Damaso de (2017)
Even with evolutions, the current Internet can not properly handle requirements such as multihoming, Quality of Service, mobility, multicasting and security. Several research groups around the world are involved in experimentally and incrementally creating the next generation of Internet architecture. Currently, knowledge and information are the factors of extreme importance for any person, company or nation. Therefore, the information security is a prerequisite for any information system. However, when the Internet was designed and security was not a necessity at the moment, this became a chronic problem in the last decades. Whenever new vulnerabilities emerge on the network, a new mechanism is created to combat this threat, so the mechanism is added to the design of the Internet as an overlay, rather than the architecture providing security intrinsically. In this way, including security aspects is a fundamental requirement for the Future Internet architecture. With regard to these architectures, Brazil has some initiatives and one of them in an ETArch. It has a conceptual view very close to the definition of Software Defined Networks and therefore since its first prototype uses the OpenFlow protocol to materialize this vision. From its creation, researchers from several universities are working to incorporate in the ETArch, in an incremental way, solutions that meet the requirements of the Future Internet. The mechanisms implementation proved viable with a reasonable average increase in time, considering the resources acquired by the mechanisms of authentication and access control incorporated into ETArch.